Indonesia Guest Comment Card Sebagai Bahan Evaluasi Kompetensi Guest Service Agent Terhadap Kepuasan Tamu Di MH Hotel Ipoh, Perak, Malaysia: Guest Comment Card Sebagai Bahan Evaluasi Kompetensi Guest Service Agent Terhadap Kepuasan Tamu Di MH Hotel Ipoh, Perak, Malaysia - Halawa fransiscus amonio; Agnes Vicky (saintmary, 2023)
The guest service area is also known as the first and the impression of the guest. This means that this is the first and last part of the guest. Hotel guests will arrive first at the guest service area and at check-out the guest must communicate with the guest service agent. So it is only natural that a deep impression will be created in the guest service area. The front office or guest service area is an information center and almost all guest activities such as receiving and sending letters, managing guest luggage, paying hotel accounts, handling lost guest items, accommodating guest complaints and also a place to provide all kinds of information both inside the hotel. or outside the hotel. Every guest who comes to the hotel to stay, for the first time is handled and managed by the guest service area by following the check-in procedure as well as when the guest leaves the hotel it will be taken care of and handled again by the guest service area by following the check-out procedure .Keywordsi: Guest Service, Competence, Guest Satisfaction